ANALYSIS OF MODERN METHODS OF ACNE DISEASE AND ITS COMPLICATIONS DIAGNOSTIC AND TREATMENT - Zapolskiy, M.E.; Svyatenko, T.V.; Zapolska, D.M. (World of Medicine and Biology, 2025)
The purpose of the study was to was to outline the main principal ways and schemes of acne and its complications diagnosis and therapy with obvious this complex skin pathology pathophysiological mechanisms understanding. The authors analyzed critically a significant mass of modern scientific foreign literature devoted to main issues of acne clinical manifestations, the features of its diagnostics in children, men and women. The data were cited concerning modern methods of this dermatological pathology treating. Scrupulous attention was attracted to contemporary data analysis on humoral, including immune mechanisms, involved into acne pathogenesis. The review also provides own authors data of clinical observations concerning post-acne complications specifics of diagnosis and treatment. A review of modern literature indicates the need to develop new diagnostic and therapeutic algorithms for acne/post-acne based on individual characteristics of the patient’s disease (hormonal background, concomitant pathology, metabolic disorders, lifestyle). Authors conclude about the importance of acne most effective methods of correction of complications use, which would allow to block effectively atrophic post-acne skin damage and achieve the maximum clinical effect in a short period of time.